Intracerebral Hemorrhage and Outcome After Thrombolysis in Stroke Patients Using Selective Serotonin-Reuptake Inhibitors. Issue 12 (December 2017) - Scheitz, Jan F.; Turc, Guillaume; Kujala, Linda; Polymeris, Alexandros A.; Heldner, Mirjam R.; Zonneveld, Thomas P.; Erdur, Hebun; Curtze, Sami; Traenka, Christopher; Brenière, Céline; Wiest, Roland; Rocco, Andrea; et al.
Abstract : Background and Purpose—: Selective serotonin-reuptake inhibitors (SSRIs) impair platelet function and have been linked to a higher risk of spontaneous intracerebral hemorrhage—an association that may be augmented by oral anticoagulants (OAC). We aimed to assess whether preadmission treatment with SSRIs in patients with acute ischemic stroke is associated with post-thrombolysis symptomatic intracerebral hemorrhage (sICH) and functional outcome. Methods—: A multicenter retrospective analysis was conducted in prospective registries of patients treated by thrombolysis within 4.5 hours of stroke onset. The association between preadmission treatment with SSRIs and sICH (ECASS II definition [European Cooperative Acute Stroke Study]) or unfavorable 3-month outcome (modified Rankin Scale >2) was assessed by logistic regression, taking into account potential interaction with concomitant use of antithrombotics. Results—: Six thousand two hundred forty-two patients were included (mean age, 70.1±14.0 years; median National Institutes of Health Stroke Scale, 9 [5–16]). Preadmission treatment with SSRIs was present in 4.3% (n=266) of patients. Overall, SICH rate was 3.9% (95% confidence interval [CI], 3.5%–4.4%; n=244), and SSRI use was not significantly associated with sICH in unadjusted (odds ratio [OR], 1.28; 95% CI, 0.72–2.27) or adjusted (OR, 1.30; 95% CI, 0.71–2.40) analysis. However, there was a significant interaction of concomitant use of OACs (international normalized ratio <1.7) and SSRI for occurrence of sICH ( P =0.01). SICH was significantly more frequent in patients taking both OAC and SSRI (23.1%; 95% CI, 8.2%–50.3%) than in patients taking OAC but not SSRI (adjusted OR, 9.04; 95% CI, 1.95–41.89). Preadmission use of SSRI was associated with unfavorable 3-month outcome (unadjusted OR, 1.90; 95% CI, 1.48–2.46; adjusted OR, 1.59; 95% CI, 1.15–2.19). Conclusions—: Preadmission treatment with SSRIs was not significantly associated with an increased risk of post-thrombolysis sICH in this cohort study. However, subgroup analysis suggested an increased risk of sICH in patients taking both SSRI and OAC. Preadmission treatment with SSRIs was associated with unfavorable outcome, which may reflect the prognostic significance of prestroke depression. Abstract : Supplemental Digital Content is available in the text.